(untitled) (American Journal of IR 4.0 and Beyond, 2023)
The movement of the Fourth Industrial Revolution is touching the manufacturing and processing industries in Bangladesh. The research uses the Fuzzy Analytical Hierarchy Process (Fuzzy-AHP) geometric mean technique, a Multi Criteria Decision Making (MCDM) methodology, to identify, analyze, and prioritize the key obstacles to Industry 4.0 implementation in Bangladesh’s Ready Made Garments (RMG) industries. Another triangular type Fuzzy-AHP extent analysis approach is applied to evaluate the minimum degree of possibilities by using fuzzy appropriateness indices and to determine the weights of assessment criteria. Pairwise comparisons are used to collect 11 experts’ preferences in verbal and numerical terms from different industries. The four main obstacles identified from related review studies are used as input variables in the Fuzzy-AHP methods to measure the intensity level of obstacles. The results have shown that the main four obstacles for Industry 4.0 are “Lack of Top Management Commitment and Owners’ Willingness” (40.6%), “Lack of Ability to Meetup Initial Investment” (30.8%), “Lack of Technical Knowledge and Education” (17.8%), and “Availability of Cheaper Labor” (10.8%). In order to avoid a null weight criterion using Fuzzy-AHP possibility extent, the weight values evaluated using Fuzzy-AHP geometric mean method are considered for decision making. The opinions or ratio scales collected from industry experts are verified with the consistency ratio checking technique.